CORRELATION BETWEEN LOCUS POLYMORPHISM OF COL11A1 GENE AND OCULAR BIOMETRY IN ACUTE AND CHRONIC PRIMARY ANGLE CLOSURE GLAUCOMA - ILAHI, FITRATUL; PRAHASTA, ANDIKA; SUSANTI, RIKA; JAMSARI, JAMSARI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of this study is to analyze the correlation between locus polymorphisms of genetics variants of rs3753841 (COL11A1) and ocular biometry, including anterior chamber depth (ACD), axial length (AL), and lens thickness (LT) in acute and chronic primary angle-closure glaucoma (PACG) patients. Methods: A total of 50 patients consisting of 25 acute PACG and 25 chronic PACG patients were included in this study. Ocular biometric parameters including anterior ACD, AL, and LT measurement were performed in all subjects using A-scan biometry. DNA isolation from blood samples was performed using PCR sequencing for genotyping locus polymorphisms of rs3753841 (COL11A1). Results: Mean ACD was shallower (2.40±0.40 mm), mean AL was shorter (21.86±1.31 mm), and mean LT was thicker (5.01±0.49 mm) in acute PACG compared to chronic PACG group, yet with no significant difference (p>0.05). We found a statistically significant difference of rs3753841 (COL11A1) polymorphism, with heterozygous mutant was mostly found in chronic PACG and homozygous mutant was mostly found in acute PACG patients (p<0.05). Significant correlations were also found between the locus polymorphism and ocular biometry (ACD and AL) in chronic PACG (p<0.05). Conclusion: We confirmed the polymorphisms of rs3753841 (COL11A1) in both groups and its significant correlation with ocular biometry (ACD and AL) in chronic PACG.